Pengaruh Capital Adequacy Ratio (CAR) dan Loan to Deposit Ratio (LDR) Terhadap Return On Assets (ROA) Pada Bank BUMN Yang Terdaftar Pada Bursa Efek Indonesia Periode 2014-2017 - Mia Saraswati; Fika Aryani (Neraca : Jurnal Akuntansi Terapan, 2019)
This research aims to examine the effect of the Capital Adequacy Ratio and Loan to Deposit Ratio on Return On Assets. The population in this research were state-owned banks listed on the Indonesia Stock Exchange quarterly period from 2014 - 2017. Sampling in this research used a saturated sample method in order to obtain a sample of 63 samples from 4 companies. This research uses a quantitative approach with the type of associative research. This research uses secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange. The data is then analyzed using multiple linear regression methods with SPSS version 24. The results of the analysis show that partially Capital Adequacy Ratio has no effect on Return On Assets. significant to Return On Assets which is shown from the results of the t test variable LDR 0,000 <0.05. Simultaneously, Capital Adequacy Ratio and Loan to Deposit Ratio have a significant effect on Return On Assets, this is indicated by the significance of the F test of 0.000 <0.05